Potential graduates’ knowledge, readiness, and disposition to 21st century employability skills in the University of Ibadan, Ibadan Nigeria (2023)
The interplay between knowledge acquisition, readiness for practical application, and the disposition of graduates towards developing and utilizing these skills is of paramount importance in the 21st1 century world of works. This study assessed potential graduates ’ knowledge, readiness, and disposition to 21st century employability skills at the University of Ibadan (UI). The study adopted a descriptive survey design. The population comprised all undergraduate students in the university. Out of 17 faculties, balloting mechanism was used to select 12 faculties. A purposive technique was used to select 590 students. A questionnaire termed Potential Graduates Employability Skills (PGES) with four subsections, was used for data collection. A descriptive statistic of percentage, frequency count, mean and standard deviation were used to analysed data collected. Result revealed that potential graduates ' knowledge was average, readiness level was high and disposition to 21st century was positive. The findings shed light on the significance of cultivating a proactive mindset, adaptability, and a commitment to continuous learning as potential graduates of the 21s' century. Furthermore, there is need for educational institutions and policymakers to prioritize the integration of 21st century employability skills within curricula, foster culture that encourages graduates’ development of these skills. Critical curriculum reforms and pedagogical innovations to enhance students’ knowledge, readiness and foster a positive disposition towards acquiring the essential skills demanded by the modern workforce is necessary at this material time.